Expanding of Life Strategies in Placozoa: Insights From Long-Term Culturing of Trichoplax and Hoilungia - Romanova, Daria Y.; Nikitin, Mikhail A.; Shchenkov, Sergey V.; Moroz, Leonid L. (Frontiers in Cell and Developmental Biology, 2022)
Placozoans are essential reference species for understanding the origins and evolution of the animal organization. However, little is known about their life strategies in natural habitats. Here, by maintaining long-term culturing for four species of Trichoplax and Hoilungia, we extend our knowledge about feeding and reproductive adaptations relevant to the diversity of life forms and immune mechanisms. Three modes of population dynamics depended upon feeding sources, including induction of social behaviors, morphogenesis, and reproductive strategies. In addition to fission, representatives of all species produced 'swarmers' (a separate vegetative reproduction stage), which could also be formed from the lower epithelium with greater cell-type diversity. We monitored the formation of specialized spheroid structures from the upper cell layer in aging culture. These 'spheres' could be transformed into juvenile animals under favorable conditions. We hypothesize that spheroid structures represent a component of the innate immune defense response with the involvement of fiber cells. Finally, we showed that regeneration could be a part of the adaptive reproductive strategies in placozoans and a unique experimental model for regenerative biology.